Some economics of abuse of dominance - Vickers, J (University of Oxford, 2007)
The paper offers an economic appraisal of selected aspects of EC law and policy towards abuse of dominance (Article 82). After a brief discussion of thresholds for dominance, five theories of exclusionary harm to compeptition are outlined, concerning: predatory pricing, partial exclusion to exploit rivals, divide-and-rule exclusion, leverage of market power, and maintenance of market power. Issues arising in three EC cases on which judgment was given in 2007 are then discussed in the light of these theories: Wanadoo (predatory pricing), British Airways (discounts and rebates), and Microsoft (refusal to supply, tying and bundling). Implications and prospects for the development of better economics-grounded EC law and policy towards abuse of dominance are discussed in conclusion.